Empowerment of Small and Medium Industries (IKM) and Value Added of Sabangs Local Souvenir Products - Riyaldi, Muhammad Haris; Umuri, Khairil; Kamal, Fakhri (Universitas Syiah Kuala, 2025)
This community service program aimed to empower Small and Medium Industries (IKMs) in Sabang City by enhancing the value-added potential of local souvenir products. The problems addressed included limited product differentiation, low-quality packaging, and inadequate branding and marketing skills among IKM actors. The program was a collaborative initiative between the Islamic Economics Study Program of Universitas Syiah Kuala and the Department of Industry, Trade, Cooperatives, and SMEs of Sabang City. Using a Service Learning (SL) approach, the activity involved workshops, product development simulations, and mentoring sessions. The results showed significant improvements, including increased participant knowledge, improved packaging quality, and the creation of actionable business plans. Over 80% of participants demonstrated enhanced entrepreneurial capacity, and more than 90% expressed satisfaction with the program. The outcomes suggest that integrated academic-community collaboration can effectively support micro-enterprise development and contribute to local economic resilience and sustainability